Preventive effectiveness of pre-employment medical assessments. Issue 1 (January 1997) - de Kort, W; van Dijk, F
Abstract : OBJECTIVE AND METHODS: Health gain, prevention of health loss, and avoidance of financial risk all seem to be driving forces for the use of pre-employment medical assessment. An attempt is made to measure the effect of implementing the pre-employment medical assessment on these end points. The anticipated maximum preventive effect (preventive effectiveness) of selection by means of pre-employment medical assessments for work related risks and the potential for disablement in individual workers can be calculated or estimated. Necessary parameters include test validity characteristics and epidemiological data for both the adverse outcome to be prevented, and risk factors of concern. RESULTS: The preventive effectiveness can be expressed as the effort (number of actions) needed to prevent one adverse event-for example, one case of occupational disease or one case of long term disablement. Actions include: a pre-employment health assessment, rejection of the candidate, individual precautions, adjustments of the job, and adjustments of the job environment. It seems that the preventive effectiveness of many actions can be low, implying that large numbers of actions are needed to prevent one adverse outcome. DISCUSSION: The medical assessment should consist of no more questions and tests than are required relevant to the stated aim. Particularly, when the pre-employment medical assessment is used to reject candidates at risk, the use of tests should be carefully weighed. If the preventive effectiveness is considered to be too low, then the question or test should not be incorporated for selection purposes. The application of a so called "expert judgment" should be based on professional guidelines wherever possible and should be made clear. The benefit of reducing the incidence of a serious adverse event by one may outweigh the costs of rejecting many candidates. CONCLUSIONS: The concept of preventive effectiveness may help to reach evidence based occupational medicine, which starts at the pre-employment medical assessment.